IMPLEMENTATION OF CONTEXTUAL TEACHING AND LEARNING (CTL) IN IMPROVING MAHARAT KITABAH IN THE ARABIC LANGUAGE DEVELOPMENT PROGRAM IN THE AL-MAWADDAH REGION - Qomariyah, Lailatul; Hidayat, M. Noer Fadli (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Most of the students of the Arabic Language Development Program in the Al-Mawaddah area of the Nurul Jadid Islamic boarding school tend to lack enthusiasm in the learning process; the students have difficulty in composing short stories in Arabic, the students lack confidence when expressing their opinions, lack of confidence, understanding of the material they obtain and placing importance on the many materials they memorize without any practice of the material or materials they get so that students quickly feel bored in learning activities. Therefore, it is necessary to apply the Contextual Teaching and Learning (CTL) learning model in the learning process because it emphasizes the whole learning process of students and connects the material they have in real life to apply it in everyday life later. The purpose of this research is 1) to determine the application of CTL in increasing the understanding of the Kitabah in the Arabic Language Development Program. 2) to determine the inhibiting and supporting factors in implementing CTL in increasing the understanding of the book in the Al-Mawaddah Region Arabic Language Development Program. 3) to find out the results of implementing CTL in increasing the understanding of the ketubah in the Al-Mawaddah Regional Arabic Language Development Program.This type of research looks for case studies using a descriptive qualitative approach. The location of this research is the PPBA Al-Mawaddah Region. The research subjects were the program coordinator, Muslimah install, and santri. Data collection uses observation, interviews, and documentation techniques. Data analysis used data reduction, data display, and conclusions.The results of this research show 1) The implementation of CTL in increasing the taharah of the ketubah in PPBA Al-Mawaddah Region is carried out 2x1 hour a week with the following steps: a. Planning stage, preparing learning materials and models by the program curriculum, b. The implementation stage is the initial stage of the ustadzah, where greetings are given, prayers are offered, Arabic language question and answer sessions are held, and assignments are collected. In the second stage, the ustadzah gives short story sentences in Indonesian, translates them into Arabic in groups, and corrects them. The third stage is concluding the material and giving homework assignments to compose, closing by providing motivation, apologizing, praying, and greeting; c. Learning evaluation, namely by assessing assignments at each meeting. 2) supporting factors include the enthusiasm of the students and ustadzah and the painstaking work of a Muslimah. 3) The results will be seen when there is a lailatul farihah event to foster students' creativity and appreciate the students' learning results for one year; apart from that, learning results are obtained by having evaluation scores above the KKM.